Analytical expression of temperature dependent electrical efficiency of N-PVT water collectors connected in series. (April 2015) - Shyam,; Tiwari, G.N.; Al-Helal, I.M.
Highlights: Analytical expressions for thermal efficiency and electrical efficiency have been derived for N PVT water collectors. Variations of different parameter with number of PVT collector and mass flow rate have been studied. Characteristics equations have been obtained for both the configurations. At medium mass flow rate the performance of both configurations were nearly same. Abstract: In the present study the series combination of N PVT water collectors, partially covered with photovoltaic module, in two different configurations namely case A: Photovoltaic module at lower portion; case B: Photovoltaic module at upper portion, have been analyzed. Analytical expressions for instantaneous thermal efficiency and temperature dependent electrical efficiency have been derived. The performances of both configurations have been compared on thermal efficiency basis and temperature dependent electrical efficiency basis. It has been concluded that at moderate mass flow rate, for large number of PVT water collectors connected in series both cases give nearly same results.